Gabapentin as an antiepileptic drug in man. Issue 6 (June 1987) - Crawford, P; Ghadiali, E; Lane, R; Blumhardt, L; Chadwick, D
Abstract : Gabapentin, 1-(aminomethyl) cyclohexane acetic acid, is a GABA analogue whose antiepileptic properties were tested in a double blind cross-over trial design as add-on therapy in a dose ranging study which compared 300 mg, 600 mg, and 900 mg/day (each dose given for 2 months) in 25 patients with severe partial and generalised epilepsies. A dose related antiepileptic effect was observed. All three doses were well tolerated and no psychometric impairment was noted. No significant drug interactions were seen. The drug appears worthy of further assessment.